Budgeting practices in some Catholic college libraries in Metro manila a survey - Rivera, Fredelina D. (Institute of Library Science, University of the Philippines Diliman, 1992)
This study was designed to determine the budgeting practices in Catholic college libraries in Metro manila. It analyzed the different sources of funds of the twenty three Catholic college libraries; the types of budgeting they adopt and the bases of their budget allocation; and the major problems/difficulties encountered in the preparation, allocation and accounting of their budgets.